Evaluating a programme for the continuing professional development of STEM teachers working within inclusive secondary schools in the UK. (2022) - Kutnick, Peter; Gartland, Clare; Good, David
Highlights: 8+ year evaluation of UK teacher STEM-CPD programme for inclusive secondary schools. Critical and theoretical appraisals of educational evaluation and CPD literatures. Bootstrapping of qualitative and quantitative methods. Provides evidence of: benefits/drawbacks of a cascade model. STEM constraints by school policy, subject disciplines and time. Networks unlikely to enhance 'communities of practice'. Length of programme experience related to positive perceptions of the programme, effects on students, feelings of STEM efficacy. 'Inclusive' teaching concerns rarely supported in classroom practices. Abstract: Preparing teachers to enhance students' STEM education usually takes place via continuing professional (CPD) programmes. Many STEM-CPD programmes are criticised for short-term, information-dominated, and non-interdisciplinary approaches that lack critical consideration of learning communities, teaching contexts or STEM teaching is likely to take place in inclusive secondary schools/classrooms. We evaluate a UK-based, national, eight-year+ STEM-CPD programme targeting inclusive secondary schools, using a bootstrapped approach combining qualitative insights and quantitative comparisons. We found high levels of teachers' STEM competence, desire for student inclusion and perceptions of student impact. Yet, shortcomings in the operations of teacher networks, lack of pedagogic/social pedagogic support and school-based disciplinary boundaries inhibited effects of the programme. Theoretical considerations were built into methods development and evaluation outcomes.